Indigenous Children Growing Up Strong : A Longitudinal Study of Aboriginal and Torres Strait Islander Families - Walter, Maggie; Martin, Karen L.; Bodkin-Andrews, Gawaian (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This edited collection by leading Australian Aboriginal scholars uses data from the Longitudinal Study of Indigenous Children (LSIC) to explore how Aboriginal and Torres Strait Islander children are growing up in contemporary Australia. The authors provide an overview of the study, including the Indigenous methodological and ethical framework which guides the analysis. They also address the resulting policy ramifications, alongside the cultural, social, educational and family dynamics of Indigenous children's lives. Indigenous Children Growing Up Strong will be of interest to students and scholars in the areas of sociology, social work, anthropology and childhood and youth studies.- Resumé vydavatel
Keywords: domorodci; děti; Austrálci; rodina; vzdělávání; indigenous peoples; children; Australian aborigines; family; education; elektronické knihy; sborníky; electronic books; papers of several authors